Prevention of cardiovascular disease in type-2 diabetes: How to improve the clinical efficacy of aspirin - Evangelista, Virgilio; Totani, Licia; Rotondo, Serenella; Lorenzet, Roberto; Tognoni, Gianni; De Berardis, Giorgia; Nicolucci, Antonio (Thrombosis and Haemostasis, 2005)
Atherosclerotic cardiovascular disease and its thrombotic complications are the principal causes of morbidity and mortality in patients with type-2 diabetes.Aspirin reduces the risk of thrombotic events in a broad range of patients with vascular disease and, in selected individuals, is beneficial for primary prevention. Although recommended by existing guidelines,in secondary and in primary prevention trials the clinical efficacy of low-dose aspirin in patients with diabetes appears to be substantially lower than in individuals without diabetes. In this review, we discuss possible mechanisms that may contribute to reduce the antithrombotic activity of aspirin in diabetes.We also discuss adjuvant therapies used in diabetic patients that may potentially improve the antithrombotic efficacy of aspirin.
Keywords: Diabetes/metabolic disorders; inflammatory mediators; platelet pharmacology